Acupressure Technique Point P6 (Nei Guan) to Reduce Nausea and Vomiting and Point L14 (Hegu) to Reduce Anxiety in Pregnant Women - Siti Mudlikah (EMBRIO: Jurnal Kebidanan, 2023)
Nausea, vomiting, and anxiety can affect the food intake of pregnant women, and nutritional deficiencies can disrupt the growth and development of the fetus in the womb. This study aims to determine the difference between pre-test and post-test after applying acupressure techniques at point P6 (Nei Guan) to reduce nausea and vomiting, and at point L14 (Hegu) to reduce anxiety. The research method used a pure experimental design. The population consisted of first-trimester pregnant women, with a sample of 30 pregnant women divided into three groups of 10 each. Groups 1 and 2 were given acupressure techniques at points P6 (Nei Guan) and L14 (Hegu) for 15 minutes every morning upon waking for 7 days, while group 3 received no treatment. Data on the acupressure technique was collected through observation, using a checklist instrument. Data on nausea and vomiting was obtained from a questionnaire. Anxiety data was obtained from the Hamilton Rating Scale for Anxiety (HRS-A). The Wilcoxon analysis was used. Group 1 had an average decrease of 1.20 in nausea and a decrease of 1.10 in anxiety. Group 2 had an average decrease of 1.20 in nausea and a decrease of 1.50 in anxiety. Group 1 showed no difference in nausea but showed a difference in anxiety. Group 2 showed a difference in both nausea and anxiety.